Managers’ support on implementation of maternal guidelines, Limpopo province, South Africa - Ireen T. Ramavhoya; Maria S. Maputle; Dorah U. Ramathuba; Rachel T. Lebese; Lizzy M. Netshikweta (Curationis, 2020)
Background: The report of Saving Mothers indicated a decline of maternal mortality from 12.8% to 12.5% last triennium of 2017. This shows that regardless of availability of national maternal health guidelines, midwives and managers, 25% of maternal deaths were caused by preventable and avoidable factors. As such, support provided by managers is vital in promoting the utilisation of maternal guidelines.